2014
DOI: 10.1007/s10571-014-0076-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulation Effects of Bone Marrow-Derived Mesenchymal Stem Cells in Xenogeneic Acellular Nerve Grafts Transplant

Abstract: This study evaluated whether bone marrow-derived mesenchymal stem cells (BM-MSCs) combined with xenogeneic acellular nerve grafts (xANGs) would reduce the inflammation reaction of xANGs transplantation. BM-MSCs were extracted, separated, purified, and cultured from the bone marrow of rats. Then BM-MSCs were seeded into 5 mm xANGs as experimental group, while xANGs group was chosen as control. Subcutaneous implantation and nerve grafts transplantation were done in this study. Walking-track tests, electrophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Despite not having found statistically significant differences in our model when comparing the groups with and without stem cells, as evidenced by other studies such as that of Zhao et al or Wang et al (Zhao et al, 2014;Wang et al, 2012), we can affirm that decellularized nervous tissue has functioned as a support structure for them, as proposed by Tang et al (Tang et al, 2013), since in fluorescence studies their survival 12 weeks post-implantation could be observed. The studies by Fan et al show a favorable effect of stem cells in terms of immunomodulatory capacity, reducing proinflammatory factors, in addition to a clear superiority of Schwann-like cells compared to stem cells from bone marrow (Fan et al, 2014a;Fan et al, 2014b). It should be noted that the study by Wang et al did not find statistically significant differences, as in our work, between acellular grafts with and without stem cells when the thickness of the myelin fibers was analyzed (Wang et al, 2012).…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Despite not having found statistically significant differences in our model when comparing the groups with and without stem cells, as evidenced by other studies such as that of Zhao et al or Wang et al (Zhao et al, 2014;Wang et al, 2012), we can affirm that decellularized nervous tissue has functioned as a support structure for them, as proposed by Tang et al (Tang et al, 2013), since in fluorescence studies their survival 12 weeks post-implantation could be observed. The studies by Fan et al show a favorable effect of stem cells in terms of immunomodulatory capacity, reducing proinflammatory factors, in addition to a clear superiority of Schwann-like cells compared to stem cells from bone marrow (Fan et al, 2014a;Fan et al, 2014b). It should be noted that the study by Wang et al did not find statistically significant differences, as in our work, between acellular grafts with and without stem cells when the thickness of the myelin fibers was analyzed (Wang et al, 2012).…”
Section: Discussionsupporting
confidence: 41%
“…Studies in animals, especially in the murine model, are increasingly common. Promising results have been obtained in their use, but the mechanism by which this benefit is obtained is not entirely clear (Fan et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to consider the pro-inflammatory and immunologic potential of decellularized nerves used as a graft. In the present review, six studies described immunological response to decellualarized grafts ( Jia et al, 2011 ; Godinho et al, 2013 ; Fan et al, 2014 ; Jiang et al, 2015 ; Wakimura et al, 2015 ; Poppler et al, 2016 ; Wang W. et al, 2016 ; Cai et al, 2017 ; Kaizawa et al, 2017 ). All six studies used immunostaining to detect T lymphocyte (CD3, CD4, CD8) and macrophage (CD68) activity.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies showed that BMSCs can induce immunosuppression by inhibiting the proliferation of T cells and the secretion of immunosuppressive factors such as interleukin-10 and transforming growth factor β [32][33][34][35][36]. This result has been further demonstrated in xenotransplantation models using donor BMSCs co-transplanted with the liver or cellular nerve grafts [32,36]. Obviously, the movement, attachment, and differentiation of BMSCs and the expression of TFPI and its effect on the coagulation need to be evaluated in vivo.…”
Section: Discussionmentioning
confidence: 99%